Coatings of FeAlCoCuNiV high entropy alloy. (2nd October 2016) - Dou, D.; Li, X. C.; Zheng, Z. Y.; Li, J. C.
Abstract : The coatings of FeAlCoCuNiV high entropy alloy were deposited by direct current magnetron sputtering. The microstructure and the mechanical and the electrochemical properties of the coatings are investigated. The coatings exhibit single FCC solid solution. The thickness of the coatings increases with the increasing deposited time. The hardness and Young's modulus of the coatings are 19.7 and 189 GPa, respectively. All coatings exhibit better electrochemical corrosion resistance than the 201 stainless steel in acidic alkali and salt corrosion mediums.